Pengaruh Permainan Tradisional Terhadap Keterampilan Berlari Dalam Pembelajaran Atletik Siswa Kelas VII SMPN 1 Karawang Barat - Haryanto, Tubagus; Ma'mun, Saepul; Yuda Kusuma, Aria (CV. ULIL ALBAB CORP, 2025)
This study aims to determine whether there is an influence of the traditional fort game on running skills in athletic learning for grade VII students of SMPN 1 Karawang Barat. This study uses a quantitative method. The population in this study was 40 students (20 control classes and 20 experimental classes). This study uses a total sampling technique, because the researcher took the entire population. Data processing was carried out using SPSS Software Version 25. The data analysis technique used was a normality test, a homogeneity test and a hypothesis test using an independent t-test. Based on the normality test, it can be seen that the data is normal because Sig> 0.05, namely in the control group a statistical test value of 0.224 was obtained, while in the experimental group a value of 0.189 was obtained. The homogeneity test is obtained if Sig> 0.05 then the data is homogeneous, while if Sig <0.05 then the data is not homogeneous. The results of the homogeneity test measurement from based on mean were 0.262, so the data was greater than 0.05, meaning a homogeneous condition. Independent t-test significance value = 0.000 less than the significance level (α) = 0.05, then H0 is rejected and H1 is accepted. This means that there is a significant difference between the average value before treatment and the average after treatment. In the t table, the calculated t is 4.390, which means that the average before treatment is lower than the average after treatment. So it can be concluded that the Bentengan Training Method can affect the running speed of students.